Agri-Food Chain Relationships - Fischer, Christian (CABI, 2014)
‘One must create bonds between men’, and – as we argue in this book – also between organizations, if a steady supply of food products is to be ensured and improved in an ever more demanding world. Against the background of global market liberalization, increasing consumer awareness and concerns, and the spreading of life-changing technologies, new ways to produce, distribute and consume food are evolving. As a result, the organization of production and distribution systems (including agriculture) has to adapt and one of the most fundamental drivers behind this process is the general recognition that, depending on the situation, collaboration can be more effective than competition as a general organizational mode to achieve economic efficiency. Collaboration requires organizations to build and maintain effective relationships, hence the need for a clear understanding of what ‘inter-organizational relationships’ are, in particular within an agri-food chain context, when they are necessary, and how they can be improved. One of the main findings from the studies in this book is that while profit motives are at the core of agri-food chain relationships, gaining full satisfaction from them also requires the nurturing of personal bonds, in particular with farmers, if a relationship is to be sustained and the mutual benefits of collaboration are to be fully unlocked.